Resolution of late-onset heart and liver failures after reversion of jejuno-ileal bypass: a case report. (3rd July 2018) - Pelà, Giovanna; De Rosa, Fabrizio; Demola, Pierluigi; Crocamo, Antonio; Missale, Gabriele; Cecchini, Stefano; Marchesi, Federico; Visioli, Francesco; Silini, Enrico Maria; Roncoroni, Luigi
Abstract: Objectives: Jejuno-ileal bypass (JIB) was a kind of bariatric surgery performed from 1960s to 1980s, able to induce sustainable weight loss by creating a surgical short bowel syndrome. Materials and methods: We report a case of an octogenarian woman who underwent in the early eighties this kind of surgery with consequent 40 kg weight loss. After 27 years, she first developed a reversible metabolic cardiomyopathy that began with signs and symptoms of heart failure. Thereafter, she was diagnosed with severe intractable liver insufficiency. Results: Despite her old age, the patient underwent reversal of JIB with consequent early improvement of hepatic function. Conclusions: This case demonstrate that in case of long-term and life-threatening complications, it is possible to successfully reverse JIB surgery after upto 30 years. The hypothesis on pathophysiology of heart and liver insufficiency are discussed.